Framing Halal Certification in Indonesia: A Diachronic Corpus-Assisted Discourse Study on Republika.co.id - Taat Budiono; Suhandano; Aris Munandar (UIN Syarif Hidayatullah Jakarta, 2026)
The implementation of Law No. 33 of 2014 on Halal Product Assurance (JPH) has transformed Indonesia's halal certification system and signaled a broader shift in the halal discourse from religious authority to state governance. This study aimed to investigate the themes and framing changes in news coverage of halal certification before and after the enactment of the JPH Law, and to examine how the media constructed the issue in two periods: 2010–2014 and 2015–2022. The study uses a Corpus-Assisted Discourse Studies (CADS) framework and the Text Linguistic Approach to Framing, and utilizes the online corpus tool Sketch Engine. The corpus consists of 1,131 halal-related news articles published by Republika.co.id from 2010 to 2022, totaling 470,404 tokens. Results show major changes both in thematic focus and media framing. The coverage between 2010 and 2014 focused on halal products, non-governmental actors (especially the Indonesian Ulema Council/MUI), and chemical substances; the coverage between 2015 and 2022 focused on government programs, state-affiliated actors, and religious issues. Regarding framing, halal certification was framed in terms of authority legitimation, consumer protection, and product quality in the earlier period, and in terms of mandatory compliance, government programs, and economic development in the latter. Overall, the implications of this study suggest that Indonesia’s transformation of its halal certification system is accompanied by a corresponding shift in halal discourse. The transfer of authority from the Indonesian Ulema Council (MUI) to the government has altered how halal is perceived and justified in public discourse. The media plays a key role in reflecting and reinforcing these shifting power dynamics among the state, religious leaders, and the marketplace.